High mountain societies and limited local resources - livelihoods and energy utilization in the Eastern Pamirs, Tajikistan - Hohberg, Georg; Kreczi, Fanny; Zandler, Harald (ERDKUNDE, 2015)
Energy supply is a key issue in isolated high mountain regions like the Eastern Pamirs of Tajikistan. This study uses an interdisciplinary approach to analyze the energy system of Alichur, an exemplary settlement in the region. Thereby, the local energy mix is evaluated, as well as the current and possible future supply of the two main resources used: Dwarf shrubs and animal manure. Finally, based on the energy system analysis, a locally adapted energy poverty index is developed. In contrast to assumptions made in the literature on the topic, we found that currently only 15 % of Alichur’s inhabitants are energy poor, 25 % are endangered by energy poverty and 60 % are energy secure. However, with decreasing access to dwarf shrubs in the future, the share of energy poor households and those endangered by energy poverty may increase to more than 70 %, leaving less than 30 % of Alichur’s households energy secure. In contrast to existing energy poverty indices, the adapted energy poverty index presented here considers social and environmental interrelationships of the case study region. It is therefore well suited for describing the energy situation of Alichur’s population.